2016
DOI: 10.4236/cs.2016.78110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High Performance Fly Ash Concrete Using Nano Silica Fume on Different Mixes

Abstract: This paper investigates the experimental results on the effect of nano silica fume on compressive strength development of concretes containing high volume fly ash (HVFA). The effect of various silica fumes contents such as 1%, 2% & 3% (wt. %) as partial replacement of cement on the compressive strength of cements is evaluated in the first part. The nano silica fume content which exhibits the highest compressive strength above is used in high volume fly ash concretes containing 30% and 50% class F fly ash. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The increased compactness and reduced permeability of concrete owing to alkali effect influence the increased strength achieved (Yatin et al, 2013). Attempts made into the durability studies of alcofine and copper slag replaced cement concrete has shown that 10% AL replacement in cement is adequate for optimus performance (Thangapandi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increased compactness and reduced permeability of concrete owing to alkali effect influence the increased strength achieved (Yatin et al, 2013). Attempts made into the durability studies of alcofine and copper slag replaced cement concrete has shown that 10% AL replacement in cement is adequate for optimus performance (Thangapandi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This means that SF has a higher influence on the bound chloride content due to carbonation than PFA. SF in comparison to PFA is likely to reduce the average pore size [54,55] for similar w/b, so the hindrance effect is more dominant in SF mixes in comparison to PFA mixes. This may explain the sustained increase in bound chlorides in 0.4 5%SF (Mix 2) and the relatively better performance of this mix over 0.4 5%PFA (Mix 5) due to the 28 days of carbonation.…”
Section: Influence Of W/b On Apparent Phmentioning
confidence: 99%